Impact of Sarcopenia on Outcomes of Autologous Head and Neck Free Tissue Reconstruction - Alwani, Mohamedkazim M.; Jones, Alexander J.; Novinger, Leah J.; Pittelkow, Eric; Bonetto, Andrea; Sim, Michael W.; Moore, Michael G.; Mantravadi, Avinash V. (Journal of Reconstructive Microsurgery, 2020)
Background Sarcopenia has been implicated as a positive predictor of postsurgical complications. Its role in head and neck (H&N) free flap reconstruction has yet to be examined. Our study aimed to determine the clinical impact of sarcopenia on postoperative outcomes in patients receiving autologous free tissue reconstruction for H&N cancer (HNC).Methods A retrospective case–control study was conducted at our tertiary referral center. Patients with HNC who received oncologic resection followed by autologous free tissue reconstruction were included. Preoperative abdominal computed tomography (CT) imaging was analyzed at the third lumbar vertebra (L3) to calculate skeletal muscle cross-sectional area (CSA, cm2). Skeletal muscle index (SMI, cm2/m2) was calculated by normalizing CSA to patient height. Sarcopenia at L3 was defined as SMI ≤ 41.6 cm2/m2 for males and ≤ 32.0 cm2/m2 for females. Data analyses were performed to compare postoperative outcomes.Results Of the 168 patients who met inclusion criteria, 47 patients (28.0%) were determined to have preoperative sarcopenia. The sarcopenic group was older (63 vs. 58 years, p = 0.017), had lower body mass index (BMI; 21.2 vs. 27.2, p < 0.001), had greater incidence of alcohol abuse (55.3 vs. 23.1%, OR = 4.11, p < 0.001). Intraoperatively, sarcopenic patients were found to have greater rates of blood transfusions (63.8 vs. 29.8%, p < 0.001). Postoperatively, sarcopenic patients had higher rates of pneumonia (p < 0.01), venous thromboembolism (p < 0.01), prolonged ventilation (p < 0.01), delirium (p < 0.01), fistula (p < 0.05), wound disruption (p < 0.05), and longer intensive care unit stays (p < 0.05). Sarcopenic patients were ultimately found to have higher overall rates of general postoperative complications (p < 0.001) and flap-specific complications (p < 0.01).Conclusion Sarcopenia was found to be a predictor of postoperative complications in H&N free flap reconstruction, signifying its value as a negative prognostic factor in surgical outcomes. This study reflects level of evidence IV.
Keywords: sarcopenia; muscle; free flap; head and neck cancer; postoperative complications